A modular design for minor groove binding and recognition of mixed base pair sequences of DNA. Issue 75 (7th September 2017) - Guo, Pu; Paul, Ananya; Kumar, Arvind; Harika, Narinder K.; Wang, Siming; Farahat, Abdelbasset A.; Boykin, David W.; Wilson, W. David
Abstract : Mixed-sequence-binding, rationally-designed heterocyclic dications specifically recognize a full turn of the DNA minor groove. Abstract : The design and synthesis of compounds that target mixed, AT/GC, DNA sequences is described. The design concept connects two N -methyl-benzimidazole-thiophene single GC recognition units with a flexible linker that lets the compound fit the shape and twist of the DNA minor groove while covering a full turn of the double helix.